2006
DOI: 10.1002/eji.200636195
|View full text |Cite|
|
Sign up to set email alerts
|

You say ITAM and I say ITIM, let's call the whole thing off: the ambiguity of immunoreceptor signalling

Abstract: Paradigms of protein tyrosine kinase (PTK)‐mediated immunoreceptor signalling have developed largely from studies of molecules containing immunoreceptor tyrosine‐based activation motifs (ITAM) and immunoreceptor tyrosine‐based inhibition motifs (ITIM). In some circumstances, ITAM can mediate inhibition and ITIM can propagate activation signals. In addition to classical immune cells, some ITAM‐ and ITIM‐encoding proteins are more widely expressed and are crucial to the development of haemopoietic cells, like os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
192
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 221 publications
(196 citation statements)
references
References 52 publications
3
192
0
Order By: Relevance
“…36 In general, receptors possessing an ITAM domain acts as activators, whereas receptors bearing an ITIM region act as inhibitors in signal transduction pathways. 37 For example, PECAM-1, which promotes migration of endothelial cells through a process relying on PTP activity, can reduce B-cell receptor-mediated calcium and tyrosine phosphorylation events because of its ITIM region. 37 Interestingly, it was reported that chimeric molecules consisting of the extracellular domain of Fc␥RIIB and the cytoplasmic portion of murine DCIR display an ITIM-mediated inhibitory role.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…36 In general, receptors possessing an ITAM domain acts as activators, whereas receptors bearing an ITIM region act as inhibitors in signal transduction pathways. 37 For example, PECAM-1, which promotes migration of endothelial cells through a process relying on PTP activity, can reduce B-cell receptor-mediated calcium and tyrosine phosphorylation events because of its ITIM region. 37 Interestingly, it was reported that chimeric molecules consisting of the extracellular domain of Fc␥RIIB and the cytoplasmic portion of murine DCIR display an ITIM-mediated inhibitory role.…”
Section: Discussionmentioning
confidence: 99%
“…37 For example, PECAM-1, which promotes migration of endothelial cells through a process relying on PTP activity, can reduce B-cell receptor-mediated calcium and tyrosine phosphorylation events because of its ITIM region. 37 Interestingly, it was reported that chimeric molecules consisting of the extracellular domain of Fc␥RIIB and the cytoplasmic portion of murine DCIR display an ITIM-mediated inhibitory role. 38 Nevertheless, in the context of our study, we did not observe any inhibitory signal mediated by DCIR at least with respect to HIV-1 biology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations